Prevalence of hypertension and its risk factors among high school children in Bangalore, India - Srirama, Srikanth; Subramanian, Mangala (International Journal Of Community Medicine And Public Health, 2020)
Background: Hypertension is a prominent health disorder that leads to 12.8% of deaths worldwide. Although predominantly considered a disorder of the adults, the roots of hypertension start from childhood. In the past children usually suffered from secondary hypertension. However, now with increased incidence of obesity, reduced physical activity, unhealthy dietary habits, use of tobacco and alcohol among adolescents there is now an increased prevalence of primary hypertension in this age group. The present study was conducted with the objective of assessing the prevalence of hypertension and its modifiable risk factors in high school children. Methods: The study was conducted among high school students aged 13 to 16 years in urban Bangalore. A self-administered questionnaire was used to assess the lifestyle. Age, sex, height, weight and resting blood pressure were recorded. Odds ratio, Chi square test and logistic regression were used in the analysis. Results: There were 550 students who participated in the study, 300 (54.54%) were males and 250 (45.45%) were females. The prevalence of prehypertension was 21.6% and hypertension was 8.9%. Logistic regression revealed that overweight, obesity, high salt intake, tobacco use, and stress were significantly associated with elevated blood pressure. Conclusions: There is a rise in the prevalence of hypertension among high school students. Changes in lifestyle seem to influence the development of hypertension in this age group. Behaviour change communication should be used to reduce the modifiable risk factors and promote healthy lifestyle among adolescents.